TREMATODOS DE LAS TORTUGAS DE MEXICO II DESCRIPTION DE UN NUEVO GENERO DE LA FAMILIA PRONOCEPHALIDAE LOOSS 1902 Y DESCRIPTION DE UNA NUEVA ESAN LUIS POTOSIECIE DEL GENERO OCTANGIOIDES PRICE 1937 - CABALLERO Y C, EDUARDO (Museo de Historia Natural, CD MEXICO, DF, MEX, 1943)
This paper con-tains: a) A redescription of H complexus; b) The de-scription of H parcivitellarius; and c) Glypthelmins californiensis which shows a large variability with regard to the size of the body and the organs, keeping as constant character t
ANS INST BIOL
Keywords: TREMATODOS, TORTUGAS, MEXICO, DESCRIPTION, NUEVO GENERO, FAMILIA PRONOCEPHALIDAE LOOSS, 1902, NUEVA ESPECIE, OCTANGIOIDES PRICE, 1937; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA MARINA